2019
DOI: 10.3389/fimmu.2019.01888
|View full text |Cite
|
Sign up to set email alerts
|

Different Expression Characteristics of LAG3 and PD-1 in Sepsis and Their Synergistic Effect on T Cell Exhaustion: A New Strategy for Immune Checkpoint Blockade

Abstract: The impairment of immunity characterized by T cell exhaustion is the main cause of death in patients with sepsis after the acute phase. Although PD-1 blockade is highly touted as a promising treatment for improving prognosis, the role of PD-1 plays in sepsis and particularly its different roles in different periods are still very limited. A recent study revealed LAG3 can resist the therapeutic effect of PD-1 blockade in tumor, which inspired us to understand their role in sepsis. We enrolled 26 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 53 publications
0
27
0
1
Order By: Relevance
“…Double-positive cells were highly activated compared to their double-negative counterparts and showed increased levels of the transcription factors T-bet and eomes in COVID-19 and malaria. A previous study by Niu et al demonstrated that the expression of PD1 and LAG-3 on T cells in patients with acute sepsis had a regulatory impact on cytokine production ( 64 ). The degree of inhibition was dependent on the expression pattern of PD1 and LAG-3 on T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Double-positive cells were highly activated compared to their double-negative counterparts and showed increased levels of the transcription factors T-bet and eomes in COVID-19 and malaria. A previous study by Niu et al demonstrated that the expression of PD1 and LAG-3 on T cells in patients with acute sepsis had a regulatory impact on cytokine production ( 64 ). The degree of inhibition was dependent on the expression pattern of PD1 and LAG-3 on T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of inhibition was dependent on the expression pattern of PD1 and LAG-3 on T cells. In comparison, single-positive PD1 − LAG-3 + T cells showed the highest cytokine production followed by single-positive PD1 + LAG-3 − T cells while double-positive PD1 + LAG-3 + T cells produced the least amount of cytokines ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, anti-LAG-3 antibody was administered in a therapeutic manner at 3 h after sepsis induction, which increases the clinical relevance. A recent study by Niu et al shows T cells co-expressing LAG-3 and PD-1 synergistically inhibit CD4 and CD8 T cells, and this correlated with increased length of hospital stay and higher mortality ( 142 ). Interestingly, this study showed that LAG-3 was only significantly elevated at day 5 post sepsis, as compared to PD-1 which was elevated early at 12 h after sepsis, indicating an important role for LAG-3 immunosuppression during progression of sepsis.…”
Section: Lymphocyte Activation-gene-3 (Lag-3) and T Cell Membrane Promentioning
confidence: 99%
“…Blocking PD-1/PD-L signaling pathways is protective in two-hit models of CLP-induced bacterial sepsis followed by fungal C. albicans infection ( 38 , 108 , 113 ). Double LAG-3 and PD-1 positive T cells show significant dysfunction and LAG-3 is upregulated later in the course of sepsis progression in patients ( 142 ). 2B4 is implicated in inhibiting the T cell specific responses, thereby compromising host immune responses ( 34 , 35 ).…”
Section: Immune Checkpoint Inhibitors As a Therapeutic Strategy To Prmentioning
confidence: 99%
“…and Niu et al also observed the opposite expression trend of LAG3 and PD-1 in sepsis and its important role in T cell exhaustion [58]. However, the role of the other immunocheckpoint molecules plays in the immunotherapy of sepsis are still limited and needs to be further explored.…”
Section: Discussionmentioning
confidence: 97%